Efeito do contraste local na modulação contextual no wulst visual de corujas suindaras (Tyto furcata) - Cíntia Aparecida de Souza Garcia (2016)
The visual perception is greatly influenced by the context, that is the manner which elements of a scene are organised into space and time. Contextual modulation is defined as the information of the receptive field periphery that modifies neuron responses. The achromatic contrast is an important property of images known to modulate neuron responses. Here we have investigated the effect of local contrast in contextual modulation by recording extra-celular signals from single neuron within the wulst. First, we described the contrast response of 31 neurons from the visual wulst of barn owls using stationary gabor patches as stimulus. We have shown that most cells exhibit a monotonic behaviour as the contrast intensity increases. Second, we applied four mathematical models (linear, power, logarithmic and hyperbolic ratio) to adjust each cell’s contrast response. According to the goodness-of-fit (R2), the hyperbolic ratio seemed to be the best describer of 78% of wulst neurons, but since the Akaike’s information criterion was employed this tendency has ceased. So we concluded that the contrast response profile was considerably variable from cell to cell. In despite of this variation, our findings reveal that a significant part of neurons (39%) exhibited linear behaviour. The results show support for previous findings that contextual modulation is engendered by the network of wulst neurons, which exhibit considerable degree of suppression (mean = 0.35). We observed that modulatory effects tend to be stronger when stimuli are collinear and placed at the end-zone suggesting that contour saliency is engendered in the visual wulst. In addition, we also noticed a tendency to facilitation effects at low contrast and suppression at high contrast conditions.The heterogeneity of the neurons responses revealed that the modulatory effects depends on the contrast and the spatial conformation of attributes. Obviously, these results does not allow us to state that processing of visual saliency happens within the visual wulst of Tyto furcata. However, facilitatory effects found in this work confirm the importance of exploring this phenomenon in detail, because its occurrence may be limited to a specific layer or population of neurons in the visual wulst that receive feedback from regions with functional correspondence extrastriatal areas of mammal brains, otherwise the operations engaged in the visual saliency must occur in a undisclosed manner within the visual wulst. Key-words: Barn owl, contrast response, contextual modulation, visual wulst.